2022
DOI: 10.1109/tvcg.2021.3114789
|View full text |Cite
|
Sign up to set email alerts
|

E-ffective: A Visual Analytic System for Exploring the Emotion and Effectiveness of Inspirational Speeches

Abstract: What makes speeches effective has long been a subject for debate, and until today there is broad controversy among public speaking experts about what factors make a speech effective as well as the roles of these factors in speeches. Moreover, there is a lack of quantitative analysis methods to help understand effective speaking strategies. In this paper, we propose E-ffective, a visual analytic system allowing speaking experts and novices to analyze both the role of speech factors and their contribution in eff… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Visualization-centered approaches present the data of presentation techniques through visualizations and further support users in gaining insights through exploration. Existing literature focuses on different purposes of speech analysis: identifying narration strategies [64], understanding emotion [67], training vocal skills [60], analyzing debate transcripts [52], exploring presentation techniques [63], decomposing humor [59], assisting the exploration of gestures [66], and analyzing the effectiveness of different speech factors [32]. While prior works have provided approaches to understand the contributions of speech factors or recommend evidence for public speaking training, our work aims at evaluating a single speech, assisting users to analyze the speech in the context of a speech collection.…”
Section: Automated Analysis Of Public Speakingmentioning
confidence: 99%
See 4 more Smart Citations
“…Visualization-centered approaches present the data of presentation techniques through visualizations and further support users in gaining insights through exploration. Existing literature focuses on different purposes of speech analysis: identifying narration strategies [64], understanding emotion [67], training vocal skills [60], analyzing debate transcripts [52], exploring presentation techniques [63], decomposing humor [59], assisting the exploration of gestures [66], and analyzing the effectiveness of different speech factors [32]. While prior works have provided approaches to understand the contributions of speech factors or recommend evidence for public speaking training, our work aims at evaluating a single speech, assisting users to analyze the speech in the context of a speech collection.…”
Section: Automated Analysis Of Public Speakingmentioning
confidence: 99%
“…The consulting firm Gartner predicts that by 2024 only 25% of business meetings are offline [46]. In the testing phase of a system including both online and offline speeches, an experienced public speaking expert reasoned that there were significant differences in the emotional expression of online and offline contests [32]. Teodorescu et al [57] found possible differences in NLP (Natural Language Processing) of titles in an online and offline contest, focused on microcontroller applications.…”
Section: Online Public Speakingmentioning
confidence: 99%
See 3 more Smart Citations